Comparative studies of antimicrobial activities of sting bee honey and stingless bee honey - Sin, Kai- Xim (2016)
Honey has been shown to have therapeutic properties, which include antibacterial activity in vitro antioxidant, anti-inflammatory, and wound healing properties In vivo. This potency is attributed to its physicochemical characteristics like moisture, pH, total phenolic content, total flavonoid content and sugar content. In the present study, antibacterial activities of sting bee honeys and stingless bee honeys were collected from different botanical and geographical origins were tested against Escherichia coli, Staphylococcus aureus and Bacillus subtilis. Physicochemical properties of these honeys were also studied to ﬁnd whether any differences in their physicochemical properties which could influence their antibacterial susceptibility. A study of Kirby-Bauer assay and Minimum Inhibitory concentration was demonstrated to indicate the antibacterial activity. This study showed that the physiochemical properties possess strong positive correlations to antibacterial activity. ln conclusion, all honeys showed significant antibacterial effect. Among the honeys analyzed, Tualang honey, Manuka honey and commercial Trigona honey demonstrated a better antibacterial property against E-coll, S.aureus and B.subtiIis when compared to Taiwan honey and raw Trigona honey at concentration 1000mg/mL in well diffusion process. ln addition, stingless bee honey like raw Trigona or commercial Trigona showed more potent against susceptible S.aureus and B.subtiIis at minimum 100mg/mL inhibitory concentration. On the other hand, Manuka honey and Tualang honey displayed higher antibacterial activities against E-coli at ranged above concentration of 100mg/mL or 125mg/mL. Meanwhile, Taiwan honey showed a fair antibacterial result at minimum 250mg/mL inhibitory concentration against E-coli, S.aureus, and B.subtilis.